2016
DOI: 10.1093/hmg/ddw010
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of BAZ1B contributes to Williams syndrome through transcriptional dysregulation of neurodevelopmental pathways

Abstract: Williams syndrome (WS) is a neurodevelopmental disorder caused by a genomic deletion of ∼28 genes that results in a cognitive and behavioral profile marked by overall intellectual impairment with relative strength in expressive language and hypersocial behavior. Advancements in protocols for neuron differentiation from induced pluripotent stem cells allowed us to elucidate the molecular circuitry underpinning the ontogeny of WS. In patient-derived stem cells and neurons, we determined the expression profile of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 85 publications
0
46
0
Order By: Relevance
“…We identified recurrent rare CNVs that overlapped with the same region that was reported in previous studies, but we did not include genes previously listed as CHD‐related candidate genes, suggesting that additional genes in these regions may be important for the cardiac phenotype. For example, our CNVs were at the 1q21.2 region but did not include the GJA5 gene.…”
Section: Discussionmentioning
confidence: 94%
“…We identified recurrent rare CNVs that overlapped with the same region that was reported in previous studies, but we did not include genes previously listed as CHD‐related candidate genes, suggesting that additional genes in these regions may be important for the cardiac phenotype. For example, our CNVs were at the 1q21.2 region but did not include the GJA5 gene.…”
Section: Discussionmentioning
confidence: 94%
“…Another gene with an intron consistently affected by decreased SMN levels both in SMA mice and the HeLa knock-down experiment was Baz1b , a transcription factor and regulator of chromatin structure recently shown to regulate the transcription of neurodevelopmental genes (85). Furthermore, Baz1b is involved in DNA damage response (86), and DNA damage is increased in SMA mouse models, including the ‘Taiwanese’ model used in this study (87).…”
Section: Resultsmentioning
confidence: 99%
“…Studying rare events that result in atypical deletions sparing different genes in the Williams syndrome critical region (WSCR), as well as single gene knock out studies in mouse models, have suggested that GTF2IRD1 and BAZ1B play a role in the craniofacial abnormalities (Ashe et al, 2008;Tassabehji et al, 2005). Likewise, the genes STX1A, LIMK1, CYLN2, BAZ1B, GTF2IRD1, and GTF2I (Dai et al, 2009;Fujiwara, Sanada, Kofuji, & Akagawa, 2016;Gao et al, 2010;van Hagen et al, 2007;Hoogenraad et al, 2002;Lalli et al, 2016;Meng et al, 2002;Morris et al, 2003;Sakurai et al, 2011) have been implicated in the cognitive and behavioral phenotypes.…”
Section: Introductionmentioning
confidence: 99%